A depth-encoding PET detector for high resolution PET using 1 mm SiPMs. (14th August 2020) - Du, Junwei; Bai, Xiaowei; Cherry, Simon R
Abstract: A dual-ended readout PET detector based on two Hamamatsu 16 × 16 arrays of 1 × 1 mm 2 SiPMs coupled to both ends of a 25 × 25 array of 0.69 × 0.69 × 20 mm 3 polished LYSOs was evaluated in terms of flood histogram, energy resolution, timing resolution, and DOI resolution. The SiPM arrays have a pitch size of 1.2 mm. Each SiPM pixel has an active area of 1 × 1 mm 2, and was fabricated using 15 μ m microcells. The LYSO array has a pitch size of 0.75 mm, and the crystals are separated using Toray reflector with a thickness of 50 μ m. The flood histogram and energy resolution were measured at different overvoltages (ranging from 1.5 to 7.0 V, in 0.5 V steps) and at four different temperatures (−7, 0, 10 and 20 °C). The timing resolution and DOI resolution were obtained at the optimal overvoltage for the flood histogram and at each different temperature. Overall, the results show better performance was obtained at lower temperatures, and that the optimal overvoltage decreased at higher temperatures. The optimal overvoltage was 5.0 V (corresponding to a bias voltage of 68.5 V) in order to achieve the highest quality flood histogram at 0 °C. Under these conditions, the flood histogram quality, energy resolution, timing resolution, and DOI resolution were 3.26 ± 0.65, 18.4 ± 4.5%, 1.70 ± 0.12 ns and 2.22 ± 0.19 mm, respectively. The flood histograms and energy resolution were also obtained at different activities. The results show that better flood histogram and energy resolution were obtained at lower activity, however all the crystals can be resolved at an event rate of over 210 k cps, indicating the DOI detector module can be used both for high resolution human brain PET and small animal PET applications.